2019
DOI: 10.21608/ejvs.2019.9820.1066
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance and physiological status of intensively raised West African dwarf (WAD) goats supplemented with dietary antioxidants

Abstract: T HIS study explored the impact of dietary antioxidant supplementation on growth performance and blood profile of intensively raised West African dwarf goats. Thirty West African dwarf goats (8.00 ± 0.13 kg) were divided into five treatment groups of six (6) animals per group and randomly allotted to one of the five diets supplemented with (1). no dietary antioxidant (control); (2). Vitamin E (200mg/kg of feed); (3).Vitamin C (600mg/kg of feed); (4). 200mg Vitamin E+ 0.2mg Selenium/kg of feed; (5). 600mg Vitam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…C increases progesterone and oestradiol synthesis, mediated by enhanced expression of the side-chain cleavage of the steroidogenic enzymes P450 cholesterol, 3ß-hydroxysteroid dehydrogenase type 1, and aromatase [21]. Yusuf et al [22] reported that supplemented vit. C with a dose of 600 mg/ kg increased cholesterol concentration in the serum of goats.…”
Section: Results and Discussion -mentioning
confidence: 99%
See 1 more Smart Citation
“…C increases progesterone and oestradiol synthesis, mediated by enhanced expression of the side-chain cleavage of the steroidogenic enzymes P450 cholesterol, 3ß-hydroxysteroid dehydrogenase type 1, and aromatase [21]. Yusuf et al [22] reported that supplemented vit. C with a dose of 600 mg/ kg increased cholesterol concentration in the serum of goats.…”
Section: Results and Discussion -mentioning
confidence: 99%
“…Vit. C inhibits the process of protein glycation and prevents the binding of glycosylation of proteins, thus lowering the level of MDA [22]. In conclusion, different effects VêO ® premium and Vitamin C supplementation were noticed on some lipid profile parameters before and during pregnancy in local Iraqi ewes exposed to heat stress.…”
mentioning
confidence: 78%